Determinación del caudal ecológico del río Paute, en base a métodos hidrológicos en el cantón Cuenca, provincia de Azuay. - Albarrasín Caldas, Katherine Paola (2021)
The ecological flow proposal was born as a solution to the alteration of ecosystems as a consequence of the detour or capture of the flow for different anthropic activities such as irrigation projects, drinking water, electricity generation, among the main ones that can be mentioned. The purpose of this research was to establish the environmental or ecological flow in the Paute River, through the hydrological station Paute Aj Dudas (H0900), using the following methods: Rafael Heras, permanence curve, Tennant or Montana and Ecuadorian Legislation; in addition to comparing the suggested flow with 10% of the average annual flow of the Paute River, to verify if it complies with the provisions of the law of water use in Ecuador. The results projected a mean interannual flow equal to 71.57 m3/s, the ecological flow of Tennant between the range 20-30%, proved to be the most appropriate to maintain the ecosystemic conditions of the channel, it exceeds the minimum flow observed within the study period (1964-2008) and complies with the provisions of the water law regarding the ecological flow.